Kajian Netnografi Aktivitas Komersialisasi Tubuh Para Kreator Onlyfans - Tsania Ghaitsa Fakhirah; Amirudin Amirudin; Af’idatul Lathifah; Arido Laksono (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The viewpoint of prostitution as something dishonor oftenly makes the world close their eyes to its presence. The motivation of man behind prostitution which always considered close with limitation of economic factor is seen underestimate either. This study aims to stop the world stick to its assumption by presenting their cognition as the result of concentrating on their voices as the actors. The scope of this study are the patterns of online prostitution in OnlyFans and the power of tactics that OnlyFans creators do to create the account or to provide 'business of imagination' (online pleasing) in Indonesia. This study was conducted by using observation, netnography, and in-depth interviews as the methods for more than three months to provide new insight to the anthropology of gender and sexuality study, as the new socio-culture phenomenon that takes place in media. The results obtained were then dissected with analysis of Foucault's thinking to the form of power relations, freedom in sexual expression, and the process of subjectification of objects as a theory that is in line with the phenomenon of online prostitution in OnlyFans. There are several patterns in undergoing OnlyFans prostitution which are fully manifested in the expression of the sexual imagination-business model in the form of photosets, rate dick pics, photobooks, content requests, personal messages, video call sex, sexting, polaroid photos, and tarot reading. While the tactics of OnlyFans’s creators do in dealing with the media blockade divided into media selection, promotion, and execution.